The Fate of Carbon in Sediments of the Xingu and Tapajós Clearwater Rivers, Eastern Amazon - Bertassoli, Dailson J.; Sawakuchi, André O.; Sawakuchi, Henrique O.; Pupim, Fabiano N.; Hartmann, Gelvam A.; McGlue, Michael M.; Chiessi, Cristiano M.; Zabel, Matthias; Schefuß, Enno; Pereira, Tatiana S.; Santos, Rudney A.; Faustino, Samantha B.; et al. (Frontiers in Marine Science, 2017)
The Xingu and Tapajós rivers in the eastern Amazon are the largest clearwater systems of the Amazon basin. Both rivers have “fluvial rias” (i.e., lake-like channels) in their downstream reaches as they are naturally impounded by the Amazon mainstem. Fluvial rias are widespread in the Amazon landscape and most of the sedimentary load from the major clearwater and blackwater rivers is deposited in these channels. So far, little is known about the role of Amazon rias as a trap and reactor for organic sediments. In this study, we used organic and inorganic geochemistry, magnetic susceptibility, diatom, and pollen analyses in sediments (suspended, riverbed, and downcore) of the Xingu and Tapajós rias to investigate the effects of hydrologic variations on the carbon budget in these clearwater rivers over the Holocene. Ages of sediment deposition (~100 to 5,500 years) were constrained by optically stimulated luminescence and radiocarbon. Major elements geochemistry and concentration of total organic carbon (TOC) indicate that seasonal hydrologic variations exert a strong influence on riverine productivity and on the input and preservation of organic matter in sediments. Stable carbon isotope data (δ13C from -31.04 to -27.49‰) and pollen analysis indicate that most of the carbon buried in rias is derived from forests. In the Xingu River, diatom analysis in bottom sediments revealed 65 infrageneric taxa that are mostly well-adapted to slack oligotrophic and acidic waters. TOC values in sediment cores are similar to values measured in riverbed sediments and indicate suitable conditions for organic matter preservation in sediments of the Xingu and Tapajós rias at least since the mid-Holocene, with carbon burial rates varying from about 84 g m-2 yr-1 to 169 g m-2 yr-1. However, redox-sensitive elements in sediment core indicate alternation between anoxic/dysoxic and oxic conditions in the water-sediment interface that may be linked to abrupt changes in precipitation. The variation between anoxic/dysoxic and oxic conditions in the water-sediment interface controls organic matter mineralization and methanogenesis. Thus, such changes promoted by hydrological variations significantly affect the capacity of Amazon rias to act either as sources or sinks of carbon.